2019
DOI: 10.1155/2019/4328219
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Hybrid Gels Made of High and Low Molecular Weight Hyaluronic Acid Induce Proliferation and Reduce Inflammation in an Osteoarthritis In Vitro Model Based on Human Synoviocytes and Chondrocytes

Abstract: High molecular weight hyaluronan (H-HA) has a pivotal role in the maintenance of normal functions of synovial fluid and structure of the articular joint, but it has been shown that its concentration is reduced in patients affected by degenerative cartilage diseases, such as osteoarthritis (OA). The aim of this study was to investigate the anti-inflammatory effects and properties of hybrid cooperative complexes based on high and low molecular weight hyaluronan (HCC) compared to H-HA on human primary cells deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 49 publications
2
44
0
Order By: Relevance
“…Indeed, the HA fragments, depending on their size, display different rheological properties and have been shown to either stimulate or inhibit inflammatory response in targeted cells and in diseased tissues, and to differently modulate the production of specific inflammatory mediators (5,6). In agreement with the notion of the size-and structure-dependent bioactivity of HA, hybrid preparations of low-and high-MW HA (7,8), crosslinked-HA (9) and hexadecylic-derivatized HA (10) show even further variations/ complexity in terms of pharmacodynamics as compared to the native, linear polymers. From the clinical point of view, according to a Cochrane Database Systematic Review analysis based on a significant number of controlled trials, it has been demonstrated that HA injections significantly reduce pain in knee osteoarthritis (11).…”
mentioning
confidence: 77%
“…Indeed, the HA fragments, depending on their size, display different rheological properties and have been shown to either stimulate or inhibit inflammatory response in targeted cells and in diseased tissues, and to differently modulate the production of specific inflammatory mediators (5,6). In agreement with the notion of the size-and structure-dependent bioactivity of HA, hybrid preparations of low-and high-MW HA (7,8), crosslinked-HA (9) and hexadecylic-derivatized HA (10) show even further variations/ complexity in terms of pharmacodynamics as compared to the native, linear polymers. From the clinical point of view, according to a Cochrane Database Systematic Review analysis based on a significant number of controlled trials, it has been demonstrated that HA injections significantly reduce pain in knee osteoarthritis (11).…”
mentioning
confidence: 77%
“…Synoviocytes cells were isolated as previously reported [16,68] from three women OA patients (58,60, and 63 years old) undergoing the surgical procedure of knee joint replacement at Orthopedics and Traumatology Department of University Federico II of Naples. The patients gave informed consent and the procedures were approved by Internal Ethical Committee.…”
Section: In Vitro Cell Cultures and Glycosaminoglycan Treatmentsmentioning
confidence: 99%
“…e bioactivity of HA in cell signaling, wound repair, morphogenesis, and matrix composition depends on its structure and biological properties [42,43]. Reviews assessing the promotion of the chondrocyte metabolism by HA [44] show that it can increase the synthetic amount of chondroitin-6-sulfate, collagen II, GAG, hydroxyproline, and DNA [45]. When delivering MSCs, HA-based hydrogels induce greater morphological differentiation of stem cells and help rebuild cartilage tissue.…”
Section: Ha-based Hydrogelsmentioning
confidence: 99%
“…When delivering MSCs, HA-based hydrogels induce greater morphological differentiation of stem cells and help rebuild cartilage tissue. Meanwhile, it also provides lubrication and buffering effects for recovering the viscosity and elasticity of synovia [44,46]. More importantly, through minimally invasive surgery, injectable HA-based hydrogels are capable of completely repairing small-scale bone and cartilage defects of any size.…”
Section: Ha-based Hydrogelsmentioning
confidence: 99%